FORMATION OF PROFESSIONAL COMPETENCE FOR NATIONAL INSTITUTIONAL TEACHERS IN THE CONDITIONS OF MODERN HIGH SCHOOL - Pal'shkova, Iryna (Mountain School of Ukrainian Carpaty, 2018)
In the article questions of formation of professional competence of the future teachers of initial classes in the conditions of modern higher educational establishment are considered. The concept of the pedagogical competence of the primary school teacher is defined and the possibilities of forming the professional and pedagogical culture of students in the modern higher school are studied. The objectives of the article: to define the concept of "professional competence of the future teacher of an elementary school" improving the level of professional competence of future primary school teachers is one of the main areas for reforming modern elementary education. That is why, at the current stage of modernization of the education system in Ukraine, issues of increasing and developing the professional competence of future teachers of the initial level are becoming particularly acute and urgent. To propose the stages of forming the professional competence of the future primary school teacher. The main indicator of the level of qualification of any modern specialist is his professional competence. The competence of a specialist can be represented as a complex of professional knowledge, skills, personal, professional qualities. The experimental program included pedagogical tasks, situations and was held in three stages. On the basis of diagnostics and testing, the levels of the formation of the professional competence of the future teacher of an elementary school were established, certain work was carried out to improve them. The analysis of the experimental material proved the relationship between the introduction of educational processes, pedagogical situations, exercises, tasks and the formation of professional competence of future teachers of elementary school. It was found that the various and interesting pedagogical tasks, situations, the more active the students perform them, and therefore the professional competence of future teachers of the elementary school is better formed. The competence of a specialist can be represented as a complex of professional knowledge, skills, relationships, professional qualities of the individual. The professional competence of the future teacher of elementary school is a factor in improving the quality of education and includes professional-content, technology and professional-personal components. The conducted research has shown the importance of introducing the results into the practice of modern high school, but does not exhaust the content of the problem being studied. In the future, this work requires the development of specific situations that are personal in the development of professional culture of future professionals.